PROPOSED CO-CREATION STRATEGY OF PAYMENT AGGREGATOR PLATFORM FOR SME BUSINESSES (CASE STUDY: PT. Moka Teknologi Indonesia) (The Indonesian Journal of Business Administration, 2019)
The growth of digital business is currently in development in every country, specifically in Indonesia. There are more easy way to easier consumer fulfill their needs on their daily activity, included in payment, buying, selling, renting, lending and funding. This digital system is changing a perspective where the traditional system mostly not used, time efficiency and easiness to access is most reason of people switching from the traditional system into technology system. Moka is one of technology start-up company pioneer that creating platform in payment aggregator and point of sales that can used by smartphone and gadgets. They currently facing challenge  while the platform is not performed as their expectation, as their co-creation strategy was implemented, when the company are collaborated in ideation process to create something valuable to the consumers. The conceptual framework that used to formulating strategy for Moka is consist of co-creation in co-definition framework, co-creation is a strategy to develop mutual understanding by collaborating with customers, determine market positioning and segmenting by STP analysis, analyzing the internal resource with VRIN and define their competitive advantage. From the external analysis, consist of social media and netnography research, in-depth interview, and company survey analysis. To get the perception of brand and services and overseeing from customer side to get significant factor to initating collaboration in co creation with Moka. The findings of this research find that some of MokaPay customer are satisfied because the usefulness of features and social belief after they use this platform. Some of MokaPay customer not satisfied because the interfaces is not attractive and communcative also the customer services is unsatisfying. The factor that defined is needed to be taken as strategy to keep existing user and enlarging customer base of MokaPay.Keywords: Point of sales, payment aggregator, Moka, co-creation, collaboration